Mechatronics - William Bolton (Longman, 1997)
Mechatronics is the integration of electronic, electrical and control engineering with computer technology to provide solution to mechanical engineering problems. This book develops subject which is incraesingly forming a crucial part in the design, manufacture and maintenance of a wide range of engineering products and processes. The clear introductory text provides a basic understanding of mechatronics and meets the requirements of the BTEC Mechtronics A and B units